IS-16 Innovation on Microfluidics-based Device for Single Cell Analysis, A Canine Cutaneous Mast Cell Tumor Model - Achariya Sailasuta; P Piyaviriyakul; T Kaewamatawong; P Theewasutrakul; D Ketpun; S Bhanpattanakul; A Pinpim; W Srituravanich; T Suwannaphan; W Jeamsaksiri; W Sripumkhai; M Chanasakulniyom (Hemera Zoa, 2018)
Recently, our laboratory, Companion Animal Cancer Research Unit, CAC-RU is interested in cancer stem cell (CSC) analysis both at the single cell and the tissue-based levels. However, cellular heterogeneity is still the major hassle for our comprehension in CSC biology. Therefore, to overcome and eradicate this big obstacles, a single cell analysis method must be established. Our laboratory has finally setup and integrated the microfluidics-based single cell analysis into our CSC researches under the association with Department of Mechanical Engineering, Faculty of Engineering, Chulalongkorn University and Thai Micro-electronic Centre, NECTEC, Ministry of Science and Technology, Thailand and Faculty of Medical Technic, Mahidol University since 2013 till present.